A database system for comparative genomic hybridization analysis. - Berrar, D. (IEEE Engineering in medicine and biology magazine)
Comparative genomic hybridization (CGH) is a molecular cytogenetic analysis method that allows the detection of chromosomal imbalances in entire genomes. The CGH approach is used in cancer research to identify over- and under-representations of chromosomal regions. To search for and analyze tumor-relevant aberration patterns in CGH data, we designed, implemented, and deployed a relational database system. This project is part of a more complex and comprehensive effort to compile, integrate, fuse, and analyze biological and clinical data from heterogeneous and distributed information sources. In this article, we discuss the obstacles and pitfalls that were encountered in the design process, describe the resulting CGH database model and the underlying technical infrastructure, and present the first results based on mining the CGH database.